USE OF CO2 LASER FOR MARKING AND CLEARING OF TEXTILE MATERIALS FOR MANUFACTURE OF MILITARY EQUIPMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In the last decades, a large application has been found by lasers in marking and cutting on textiles, plexiglass, wood, metals and other materials. These items apply to both the military and the economy of the countries of the world. A group of Bulgarian students from the National Military University Vasil Levski, led by Dr. Nikolay Dolchinkov, conducted a research with a group of TAR under the leadership of Prof. Lubomir Lazov at the Laser Center in Rezekne at the end of 2018. The report shows the achieved results and the relevant analyzes. Graphically and tabularly, the dependence of the depth of the markings and the cut-off of the power and speed of the used CO2 laser are presented.